Basic characterization and investigation of a fluorinated terpolymer in pure state and in mixtures with kaolinite at solid interphases of thin films prepared by facile solution cast and nonsolvent methods. (November 2014) - Ok, Salim; Sadaf, Shamaila; Walder, Lorenz
In this work, both basic characterization and solution cast thin films of a fluorinated terpolymer of tetrafluoroethylene (TFE), hexafluoropropylene (HFP), and vinylidene fluoride (VDF), known as THV, are studied. Thermal analysis of the terpolymer depicted a broad melting temperature, and thermal degradation started at 170 K above the melting temperature. Solution fluorine 19 nuclear magnetic resonance results revealed that THV 221G has higher TFE content than those of HFP and VDF. Increase in water contact angle is observed in thin films prepared from THV in pure state by the more specific nonsolvent preparation technique. By the same specific method, a similar increase is seen in thin films prepared from mixtures of polymer and kaolinite. Upon mixing the terpolymer of THV with hydrophilic kaolinite, a natural mineral, it is still possible to obtain rough and hydrophobic surfaces. The highest contact angle was obtained upon using the facile nonsolvent approach. Further, preparing the thin films with the addition of the hydrophilic mineral did not change the hydrophobic character of the films.